Pure laparoscopic versus robotic liver resections: Multicentric propensity score‐based analysis with stratification according to difficulty scores. (3rd August 2021) - Cipriani, Federica; Fiorentini, Guido; Magistri, Paolo; Fontani, Andrea; Menonna, Francesca; Annecchiarico, Mario; Lauterio, Andrea; De Carlis, Luciano; Coratti, Andrea; Boggi, Ugo; Ceccarelli, Graziano; Di Benedetto, Fabrizio; et al.
Abstract: Background: The benefits of pure laparoscopic and robot‐assisted liver resections (LLR and RALR) are known in comparison to open surgery. The aim of the present retrospective comparative study is to investigate the role of RALR and LLR according to different levels of difficulty. Methods: The institutional databases of six high‐volume hepatobiliary centers were retrospectively reviewed. The study population was divided in two groups: LLR and RALR. The procedures were stratified for difficulty levels accordingly to three classifications. A propensity score matching was implemented to mitigate selection bias. Short‐term outcomes were the object of comparison. Results: Nine hundred and thirty‐six LLR and 403 RALR were collected. RALR exhibited fewer cases of intraoperative blood loss, lower transfusion and conversion rates (especially for oncological radicality) than LLR in the setting of highly difficult operations, whereas LLR had lower postoperative morbidity and fewer low‐grade complications. For intermediate and low‐difficulty resections, the intraoperative advantages of RALR gradually decreased to nonsignificant results and LLR remained associated with lower postoperative morbidity. Conclusion: Robot‐assisted liver resections do not show operative nor clinically significant benefits over LLR for low‐ and intermediate‐difficulty resections. By reducing conversion rates, RALR can favour the operative feasibility of difficult resections possibly extending the indications of minimally invasive approaches for liver resection.